Pengaruh Social Media Marketing, Harga dan Kepercayaan Merek Terhadap Keputusan Pembelian (Studi Kasus pada TSB.Encore) - Jessy Rucci; Mariah (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to find out whether there is an influence of interaction design, customer review and promotion on the assessment of online credibility on tokopedia application. This study used validity tests, reliability tests, multiple linear regression tests, and hypothesis tests both partial and simultaneous with the help of spss version 20 programs. The sample was taken by 185 respondents. The research uses quantitative approach with purposive sampling technique method. Data collection is done by disseminating questionnaires using the Likert scale to measure each statement. The results showed that there is a positive and significant influence between interaction design, customer review and promotion on online credibility assessment on Tokopedia application.